Shear strengthening of damaged reinforced concrete beams with hybrid composite plates - Baghi, Hadi (2015)
This paper aims to evaluate experimentally the potentialities of Hybrid Composite Plates (HCPs) technique for the shear strengthening of reinforced concrete (RC) beams that were previously subjected to intense damage in shear. HCP is a thin plate of Strain Hardening Cementitious Composite (SHCC) reinforced with Carbon Fiber Reinforced Polymer (CFRP) laminates. For this purpose, an experimental program composed of two series of beams (rectangular and T cross section) was executed to assess the strengthening efficiency of this technique. In the first step of this experimental program, the control beams, without steel stirrups, were loaded up to their shear failure, and fully unloaded. Then, these pre-damaged beams were shear strengthened by applying HCPs to their lateral faces by using a combination of epoxy adhesive and mechanical anchors. The bolts were applied with a certain torque in order to increase the concrete confinement. The obtained results showed that the increase of load carrying capacity of the damaged strengthened beams when HCPs were applied with epoxy adhesive and mechanical anchors was 2 and 2.5 times of the load carrying capacity of the corresponding reference beams (without HCPs) for the rectangular and T cross section beam series, respectively. To further explore the potentialities of the HCPs technique for the shear strengthening, the experimental tests were simulated using an advanced numerical model by a FEM-based computer program. After demonstration the good predictive performance of the numerical model, a parametric study was executed to highlight the influence of SHCC as an alternative for mortar, as well as the influence of torque level applied to the mechanical anchors, on the load carrying capacity of beams strengthened with the proposed technique.